If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2g+6)=48
We move all terms to the left:
3(2g+6)-(48)=0
We multiply parentheses
6g+18-48=0
We add all the numbers together, and all the variables
6g-30=0
We move all terms containing g to the left, all other terms to the right
6g=30
g=30/6
g=5
| 5y-3y-4=37.44 | | (X+4)(x)=45 | | 4(4+2)=3(v+5) | | 11y-6y-13=85.55 | | 4x-5=90° | | (X+10)(x)=11 | | 8y-3y-5=83.60 | | y+15=-25 | | 9=3.x | | 2x+5.7=2.4 | | 11x-30=5x+3 | | 4x-16=8x+14 | | x2-7x+21=0 | | 8x+14=4x-16 | | 2x+7x=180° | | 17^8x=9^x-3 | | 48-10x=10+9x | | m=-7;(4,2) | | 3/20=45/x | | -7(x)=-91 | | 0.24x=4 | | 10c+6=166 | | 6x+15=3(x+5)-(x-2)+1 | | 46+43x=146+43x=1 | | 6x+15=3(x+5)-(x-2) | | 3x+6=1/3(6x-15 | | n/4=15/20 | | 3m+6=1/3(6m-15 | | z+2.5=3.2+5.2 | | 9x-43=3x+21 | | z+2.5=3.2z=5.2 | | z+2.5=3.2=5.2 |